SCENARIOS FOR THE DEVELOPMENT OF UKRAINE’S WATER INFRASTRUCTURE UNTIL 2035: EUROPEAN APPROACHES TO ECONOMIC MODELING AND RISK ANALYSIS - Krylov, Maksym; Hbur, Zoriana (Public Management and Policy, 2025)
The article examines scenarios for the development of Ukraine’s water infrastructure up to 2035, taking into account European approaches to economic modeling and risk analysis. It has been established that the vulnerability of Ukraine’s water sector is caused by military destruction and, at the same time, long-term climate risks, which determine the framework for possible development scenarios. It is emphasized that the energy crisis is an additional barrier to the stable functioning of water management systems, since the energy intensity of water supply in Ukraine is almost twice the European average. It is determined that the tariff policy needs to be revised, taking into account a risk-oriented approach that allows increasing the system’s resilience to crisis impacts. It is noted that the war has caused large-scale destruction of infrastructure and significantly increased financial needs, which are estimated at 11.3 billion over the next decade. It was outlined that the modernization of sewage treatment plants and water supply systems requires the largest investment costs, which are priority areas for recovery. Regional differentiation in the level of wear and tear of water supply networks was considered, which demonstrates the instability of modernization processes and significant disparities between regions. It has been found that local investment programs can temporarily improve the situation, but their unevenness creates unstable dynamics. It is emphasized that crisis conditions, in particular the war, have caused a sharp deterioration in indicators in a number of regions, which needs to be taken into account in forecast scenarios. The importance of using European risk analysis methods to model the relationship between financial, technological, and security parameters is emphasized. It is noted that the implementation of European directives into the national legal system forms the basis for harmonizing standards and creating a comprehensive development strategy. The importance of the Concept of State Programs in the Field of Water Supply and Sanitation Modernization, aimed at integrating environmental, technical, and social aspects, was determined. It was noted that the implementation of EU directives on drinking water quality, wastewater treatment, and water resource management ensures the integration of risk management and digital technologies into planning processes. It has been established that digitalization, which is actively used in EU countries, is gradually becoming a determining factor in improving the efficiency of water system management and quality monitoring. It has been emphasized that the strategic course towards European integration provides for the transformation of the industry in accordance with the principles of a “green” economy and environmental sustainability.